On Moral Nose - Turoldo, Fabrizio (2024)
There are many authors who consider the so-called "moral nose" a valid epistemological tool in the field of morality. The expression was used by George Orwell, following in Friedrich Nietzsche’s footsteps and was very clearly described by Leo Tolstoy. It has also been employed by authors such as Elisabeth Anscombe, Bernard Williams, Noam Chomsky, Stuart Hampshire, Mary Warnock, and Leon Kass. This article examines John Harris’ detailed criticism of what he ironically calls the "olfactory school of moral philosophy." Harris’ criticism is contrasted with Jonathan Glover’s defense of the moral nose. Glover draws some useful distinctions between the various meanings that the notion of moral nose can assume. Finally, the notion of moral nose is compared with classic notions such as Aristotelian phronesis, Heideggerian aletheia, and the concept of "sentiment" proposed by the philosopher Thomas Reid. The conclusion reached is that morality cannot be based only on reason, or—as David Hume would have it—only on feelings.
Keywords: Aristotle; Bernard Williams; David Hume; G.E.M. Anscombe; George Orwell; John Harris; Jonathan Glover; Leo Tolstoy; Leon Kass; Martin Heidegger; Mary Warnock; Noam Chomsky; Stuart Hampshire; Thomas Reid; aletheia; deliberative desire; desiderative understanding; moral nose; Phronesis; sentiment; thought-involving desire